Melayani dengan Senyum, Bertahan dengan Rasa: Analisis Kepedulian Konsumen pada Usaha RM Ayam Pasundan - Intan Anggraeni Aulia Putri; Farhan Farhan; Muhamad Rizky Pratama; Widya Ananda Pangestu; Nuhiyah (Jurnal Manajemen, 2026)
This study aims to understand how customer care is implemented through service and product quality at RM Ayam Pasundan, as well as its impact on customer trust and loyalty. Efforts to maintain good communication with customers also help the business owner understand their needs and expectations. This strengthens long-term relationships between customers and RM Ayam Pasundan while enhancing the restaurant’s reputation in the community. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. The results show that customer care is reflected in friendly and empathetic service and the consistency of taste and product quality. The business owner maintains honesty, respect, and product integrity even when raw material prices increase, allowing customers to remain loyal despite changes in the business location. This study emphasizes that customer care and quality consistency are key factors in building trust and loyalty, while also reflecting the application of human values in the culinary business. These findings indicate that the implementation of simple business ethics can significantly enhance customer satisfaction and sustain long-term customer relationships.